Individualized Homoeopathy in the Treatment of Seborrheic Dermatitis: An Evidence-Based Clinical Case Report (Advancements in Homeopathic Research, 2022)
Seborrheic dermatitis is a chronic or relapsing skin condition that mainly affects the scalp. It causes greasy skin covered with flaky white or yellow scales or crust, red skin, itching and dandruff. Seborrheic dermatitis also affect oily areas of the body, such as the face, sides of the nose, eyebrows, ears, eyelids and chest. Homoeopathy has a useful role for different types of skin diseases which also includes seborrheic dermatitis. The medicine selection will be based on the individual symptoms of the patient and not on the pathological entity of seborrheic dermatitis. One such documented case report of a particular patient is illustrated in the following article, where Hepar sulph was prescribed based on constitutional totality after considering generalities, particulars and miasmatic background. The improvement was documented by modified SCORAD (Scoring Atopic Dermatitis) and photographic evidence changes during every follow-up. Within a significant time frame, all lesions of seborrheic dermatitis were annihilated.
Keywords: Seborrheic dermatitis; Homoeopathy; Hepar sulphuris calcareum